リニア振動アクチュエータを用いた触覚提示システムの開発 - 鈴木, 隆史; 曲谷, 一成 (Transactions of Japanese Society for Medical and Biological Engineering, 2016)
The objective of this study is the development of the device gives direction of power for the human. The device made up of 4 stack linear oscillatory actuators on 3 axis. These actuators are mounted on the ball-like metallic frame that is 40 mm diameter. We can feel the direction of power using this device. Displayed angles transform Spherical Polar Coordinates. The microprocessor makes PWM based on Spherical Polar Coordinates. PWM signals drive 12 actuators. In the future, it will be possible to guide the visually-impaired in arbitrary direction.